Stability Analysis of Continuous-Time Switched Neural Networks With Time-Varying Delay Based on Admissible Edge-Dependent Average Dwell Time - Wang, Hui-Ting; He, Yong; Zhang, Chuan-Ke (IEEE transaction on neural networks and learning systems, 2021)
This article investigates the stability of the switched neural networks (SNNs) with a time-varying delay. To effectively guarantee the stability of the considered system with unstable subsystems and reduce conservatism of the stability criteria, admissible edge-dependent average dwell time (AED-ADT) is first utilized to restrict switching signals for the continuous-time SNNs, and multiple Lyapunov-Kravosikii functionals (LKFs) combining relaxed integral inequalities are employed to develop two novel less-conservative stability conditions. Finally, the numeral examples clearly indicate that the proposed criteria can reduce conservatism and ensure the stability of continuous-time SNNs.